Public Sector Bargaining - Boivin, Jean (Relations Industrielles / Industrial Relations, 1989)
This article reviews the book, "Public Sector Bargaining," by Benjamin Aaron, Joyce M. Najita & James L. Stern.

Cleared for Takeoff : Airline Labour Relations since Deregulation - Boivin, Jean (Relations Industrielles / Industrial Relations, 1989)
This article reviews the book, "Cleared for Takeoff : Airline Labour Relations since Deregulation," by Jean T. Mckelvey.